Analysis of the Application of Emkm SAK in the Preparation of Financial Statements in the Sakti.Online Application - Hijjah, Warnida; Kartini, Tina; Indrawan, Andri (International Journal of Law Policy and Governance, 2023)
The purpose of this study is to analyze the application of SAK EMKM in the preparation of financial statements produced by the cooperative application system, namely SAKTI. Online. The research was conducted at the Nurul Iman Cooperative. This research uses qualitative methods with a type of comparative descriptive approach that will later describe, describe and compare theory and actual practice so that conclusions can be drawn. Data were obtained using observation, interview, and documentation techniques. The results of the study concluded that the financial statements of the Nurul Iman Cooperative were presented using the SAKTI.Online Applications were not by SAK EMKM completely because they had not presented the three components of financial statements according to SAK EMKM. The preparation of the Nurul Iman Cooperative financial statements was presented using the SAKTI.Online application only presents the balance sheet (statement of financial position), and the calculation report of operating results (income statement) but has not presented notes to the financial statements.